2012
DOI: 10.1002/cne.23154
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic signal optical imaging evidence for dorsal V3 in the prosimian galago (Otolemur garnettii)

Abstract: Currently, we lack consensus regarding the organization along the anterior border of dorsomedial V2 in primates. Previous studies suggest that this region could be either the dorsomedial area, characterized by both an upper and a lower visual field representation, or the dorsal aspect of area V3, which only contains a lower visual field representation. We examined these proposals by using optical imaging of intrinsic signals to investigate this region in the prosimian galago (Otole-mur garnettii). Galagos repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Similar organizational schemes have been proposed for New World monkeys (e.g. Lyon and Kaas, 2001;2002a) and Prosimians (Fan et al, 2012;Lyon and Kaas, 2002b), although the majority of New World monkey studies favour alternative models (e.g. Figure 1B, C).…”
Section: Introductionmentioning
confidence: 56%
“…Similar organizational schemes have been proposed for New World monkeys (e.g. Lyon and Kaas, 2001;2002a) and Prosimians (Fan et al, 2012;Lyon and Kaas, 2002b), although the majority of New World monkey studies favour alternative models (e.g. Figure 1B, C).…”
Section: Introductionmentioning
confidence: 56%
“…One important development has been data indicating that there are likely to be multiple types of cortical drivers (Sherman and Guillery,2011; Viaene et al,2011; Wei et al,2011). Another development suggests that, at least in the mouse, there are both driver and modulator class reciprocal connections from the primary sensory cortices to adjoining cortices (Covic and Sherman,2011; De Pasquale and Sherman,2011). This second point finds some support from the work of Soares et al (2004), who, working with the cebus monkey, showed a mixture of both excitation and inhibition of V2 responses after pulvinar blockade with GABA.…”
Section: Discussionmentioning
confidence: 99%
“…1A, left). This model is based on electrophysiological recordings and anatomical studies in Old World monkeys (Zeki, 1978; Gattass et al, 1988; Kaas & Lyon, 2001; Lyon & Kaas, 2001), but also has been reported in New World monkeys (Lyon et al, 2002) and prosimians (Fan et al, 2012) using optical imaging. Similar to area V2, area V3 is proposed to form a “second-order” representation of visual space with a discontinuity in the representation of the horizontal meridian that anatomically separates upper and lower visual field representations in ventral and dorsal occipital cortex, respectively.…”
Section: Identification Of Individual Areasmentioning
confidence: 99%